Music‐Evoked Images: Music that Inspires Them and Their Influences on Brand and Message Recall in the Short and the Longer Term. Issue 10 (October 2014) - Fraser, Cynthia
ABSTRACT Prior research studies of music‐background influences on brand message recall following ad exposure have produced equivocal results, possibly due to the practice of comparing presence or absence of music. This research moves beyond the presence or absence of background music to quantify the range of impacts on brand message recall created by multiple, diverse music backgrounds. Music backgrounds differ widely and prompt music‐evoked images (MEIs), both private, personal images forged during previous listening experiences, and connoted images common to multiple listeners, motivated by structural cues. Personally relevant private MEIs may have the unintended effect of interfering with brand message processing, integration, and recall, where nonbrand images are also prompted; nonetheless, prolonged processing of those MEIs may enhance chance of association between the music and brand and message elements, offering the intended effect of facilitating later music‐cued brand message recall. Impersonal, connoted MEIs may reinforce brand and message elements, improving brand message integration and recall and avoiding processing interference; however, with briefer processing, and without prior personal associations, the music may be less likely linked to brand and message elements and less effective in facilitating later music‐cued recall. Results of an experiment using multimedia ads for multiple brands with a diverse set of music backgrounds support the hypothesized influences of private and connoted MEIs.